The effects of contact with farmers on the hunter-gatherers' lithic assemblages: use-wear analysis of stone tools from Holkrans, North West Province, South Africa - Law de Lauriston, P.B. MacLaren (My University, 2015)
Early contact between Later Stone Age hunter-gatherers at Holkrans rock shelter (BFK 1), in the Vredefort Dome, North West Province, South Africa, and food producers occurred within the last 500 years. Evidence presented in this study suggests that a more probable time frame was sometime between the early 16th and 17th centuries AD. Holkrans chronology comprises two phases, pre-ceramic and ceramic, with three superimposed components: a lower, pre-contact/ pre-ceramic period; a middle, early contact/ ceramic period; and a terminal period. Use-wear analysis of lithics from the lower and middle components provided the medium through which changes or continuity in cultural and behavioural practices between the pre-contact/ pre-ceramic and early-contact/ ceramic periods were interpreted, with a view to shedding light on the nature and impact of contact on the shelter’s hunter-gatherers with food producers. The results of analysis, supported by additional archaeological evidence, suggest that the Holkrans hunter-gatherers experienced early contact and subsequent interaction with food producers as an ‘extended pioneer phase’. Over time, as food producers subdued land and began to permanently settle in the area, the Holkrans hunter-gatherers appear to have maintained this extended pioneer phase; that is, a primarily hunter-gatherer way of life up to the terminal occupation of the shelter, probably in the early 19th century. iii
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2014.
Keywords: Hunting and gathering societies.; Archaeology - South Africa - North West.